Impulse Excitation in a Watertight Steel Circular Cylindrical Shell and Influence of Structural Configuration on Underwater Radiated Noise - WU, Chen-I; TOO, Gee-Pinn; WU, Bo-Hsien (Archives of Acoustics, 2023)
This study used experimental measurements and the finite-element method (FEM) simulations to investigate transient underwater radiated noise induced by the impulse excitation of water surrounding a watertight steel-structured circular cylindrical shell submerged in the 176 × 8 × 4 m towing tank. The excitation was caused by dropping an iron block onto a structural bracket in the shell to generate structural vibration. The experimental results were found to be consistent with the FEM results, with the difference between the experimental and simulated sound pressure levels being less than 3 dB. Moreover, it was determined that the structural vibration also generated airborne noise in the cylindrical shell, but this contributed much less than the impulse excitation to the induction of underwater radiated noise. Finally, analysis of the sound field of the underwater noise radiation showed that it was influenced by the wall thickness of the watertight steel cylindrical shell and that of the reinforced bracket seat structure. In particular, the structural reinforcement position proved to be the diffusion breakpoint of the underwater sound radiation. This demonstrates that compared with the studied structure, a thicker and more complex reinforced structure will transmit less or incomplete sound radiation into water.